2019
DOI: 10.3389/fneur.2019.00824
|View full text |Cite
|
Sign up to set email alerts
|

Dental Pulp Stem Cells: An Attractive Alternative for Cell Therapy in Ischemic Stroke

Abstract: Ischemic stroke is a major cause of disability and mortality worldwide, but effective restorative treatments are very limited at present. Regenerative medicine research revealed that stem cells are promising therapeutic options. Dental pulp stem cells (DPSCs) are autologously applicable cells that origin from the neural crest and exhibit neuro-ectodermal features next to multilineage differentiation potentials. DPSCs are of increasing interest since they are relatively easy to obtain, exhibit a strong prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
83
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 132 publications
0
83
0
4
Order By: Relevance
“…Recently, isolation and characterization of DPSCs from a "discarded" supernumerary tooth were primarily achieved by Huang and his colleagues [15]. Meanwhile, numerous investigators have also proactively explored the efficacy of these advantaged stem cells in various systemic disease treatment, including diabetes, muscular dystrophy, ischemic stroke, Alzheimer's disease, and eye disease [16,17]. Unexpectedly, by practicing comparative analysis, Lee et al and Seo et al recently reported other subtypes of stem cells from human exfoliated deciduous teeth (SHED) and periodontal ligament stem cells (PDLSCs), which were distinguished from DPSCs, respectively [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, isolation and characterization of DPSCs from a "discarded" supernumerary tooth were primarily achieved by Huang and his colleagues [15]. Meanwhile, numerous investigators have also proactively explored the efficacy of these advantaged stem cells in various systemic disease treatment, including diabetes, muscular dystrophy, ischemic stroke, Alzheimer's disease, and eye disease [16,17]. Unexpectedly, by practicing comparative analysis, Lee et al and Seo et al recently reported other subtypes of stem cells from human exfoliated deciduous teeth (SHED) and periodontal ligament stem cells (PDLSCs), which were distinguished from DPSCs, respectively [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Under low LPS concentration, overexpressed TLR4 activates intracellular NF-κB signalling pathway, mediating effective production of cytokines, activation of innate immunity and proliferation of younger DPSCs, in contrast to the aged ones. Furthermore, not only the proliferation capacity decreased with age under induced inflammation, but more importantly the expression of genes responsible for mineralization [13].…”
Section: Proliferation Differentiation and Mineralizationmentioning
confidence: 99%
“…SCRM overcomes the heterogeneity issues and, hence, gets rid of double positive results in ex vivo studies, such that bio function and phenotypic differences of DPSCs are distinguished by variability in nucleic acid, lipid and protein compartments. As a consequence, it is possible to separate stem cells by age, proliferation capacity, viability and senescence [13].…”
Section: Culture and Isolationmentioning
confidence: 99%
“…Herein, it is important to emphasize that the general characteristics and immunophenotype define DPSCs as a population resembling "mesenchymal stem/stromal cells" (MSCs), as it was also postulated by Ledesma-Martinez et al in 2016. However, some investigators have pointed out that the exact status of DPSCs as a MSC population is still not fully defined and requires further investigations (Lan et al, 2019). However, taking into consideration that stem/ stromal cells isolated from different tissues are today classified as MSCs when they fulfill the "MSC classification criteria" published by ISCT, we may consider DPSCs as a MSC population, but we should still consider their unique properties, including developmental origin.…”
mentioning
confidence: 99%
“…Recently, Lan et al reviewed the use of DPSCs in a rodent stroke model. In all publications considered by authors of that review, the use of DPSCs has led to a significant improvement of brain function or a decrease in the infract size after stroke (Lan et al, 2019).…”
mentioning
confidence: 99%